Wnt5A promotes an adaptive, senescent‐like stress response, while continuing to drive invasion in melanoma cells. (29th December 2014) - Webster, Marie R.; Xu, Mai; Kinzler, Kathryn A.; Kaur, Amanpreet; Appleton, Jessica; O'Connell, Michael P.; Marchbank, Katie; Valiga, Alexander; Dang, Vanessa M.; Perego, Michela; Zhang, Gao; Slipicevic, Ana; et al.
Abstract We have previously shown that Wnt5A drives invasion in melanoma. We have also shown that Wnt5A promotes resistance to therapy designed to target the BRAFV600E mutation in melanoma. Here, we show that melanomas characterized by high levels of Wnt5A respond to therapeutic stress by increasing p21 and expressing classical markers of senescence, including positivity for senescence‐associated β‐galactosidase (SA‐β‐gal), senescence‐associated heterochromatic foci (SAHF), H3K9Me chromatin marks, and PML bodies. We find that despite this, these cells retain their ability to migrate and invade. Further, despite the expression of classic markers of senescence such as SA‐β‐gal and SAHF, these Wnt5A‐high cells are able to colonize the lungs in in vivo tail vein colony‐forming assays. This clearly underscores the fact that these markers do not indicate true senescence in these cells, but instead an adaptive stress response that allows the cells to evade therapy and invade. Notably, silencing Wnt5A reduces expression of these markers and decreases invasiveness. The combined data point to Wnt5A as a master regulator of an adaptive stress response in melanoma, which may contribute to therapy resistance.